2013
DOI: 10.3177/jnsv.59.343
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Pyridoxal 5'-Phosphate Concentration during Pregnancy Stages in Japanese Women

Abstract: Most Japanese women do not consume the estimated average requirement of vitamin B6 (1.7 mg/d) during pregnancy. Nevertheless, these deficiencies are not reported. We investigated a nutritional biomarker of vitamin B6 in pregnant Japanese women as well as their vitamin B6 intakes. Vitamin B6 intakes in the first, second, and third trimesters of pregnancy, and 1 mo after delivery were 0.79±0.61 (n=56), 0.81±0.29 (n=71), 0.90±0.35 (n=92), and 1.00±0.31 (n=44) mg/d, respectively. Plasma pyridoxal 5'-phosphate (PLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Maternal plasma PLP concentrations decreased from early to late pregnancy in our study, which is consistent with previous observations (Fayyaz et al, ; Shibata et al, ; Takimoto et al, ). Interestingly, there were distinct opposing trends across pregnancy depending on the mother's plasma PLP status in early pregnancy: Plasma PLP concentrations increased during pregnancy in those with plasma PLP concentrations <20 nmol/L in early pregnancy, and the opposite trend was observed in those with plasma PLP concentrations ≥20 nmol/L in early pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Maternal plasma PLP concentrations decreased from early to late pregnancy in our study, which is consistent with previous observations (Fayyaz et al, ; Shibata et al, ; Takimoto et al, ). Interestingly, there were distinct opposing trends across pregnancy depending on the mother's plasma PLP status in early pregnancy: Plasma PLP concentrations increased during pregnancy in those with plasma PLP concentrations <20 nmol/L in early pregnancy, and the opposite trend was observed in those with plasma PLP concentrations ≥20 nmol/L in early pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, 6.8% and 14.3% of women had plasma PLP <30 nmol/L in early pregnancy and at delivery, respectively. A study from Japan found 16%, 82%, and 84% of pregnant women had plasma PLP concentrations <30 nmol/L in the 1st, 2nd, and 3rd trimesters, respectively (Shibata et al, ). This is not surprising considering these women were not taking supplements, and their dietary vitamin B 6 intakes were considerably low (<1.0 mg per day; Shibata et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Folate, cobalamin, and PLP tend to decrease, whereas riboflavin is reported to show only minor changes during pregnancy [38,39,40,41,42]. tHcy, a marker of folate and cobalamin deficiency [43], is 30%–60% lower in pregnant compared to nonpregnant women, with the lowest levels seen in the second trimester [44].…”
Section: Discussionmentioning
confidence: 99%